Deciphering the compatibility rules of traditional Chinese medicine prescriptions based on NMR metabolomics: A case study of Xiaoyaosan. (23rd May 2020) - Liu, Xiaojie; Lv, Meng; Wang, Yaze; Zhao, Di; Zhao, Sijun; Li, Shunyong; Qin, Xuemei
Abstract: Ethnopharmacological relevance: Xiaoyaosan (XYS), a represent and classic TCM prescription, consists of Radix Bupleuri, Radix Angelicae Sinensis, Radix Paeoniae Alba, Rhizoma Atractylodis Macrocephalae, Poria, Herba Menthae, Rhizoma Zingiberis Recens and Radix Glycyrrhizae . XYS can sooth the liver and strengthen the spleen through improving the circulation of qi and nourishing blood according to the TCM theory, therefore exhibiting anti-depression effects. Aim of the study: This study was conducted to investigate the compatibility rule of antidepressant effect of XYS by using both the "Efficacy Compositions" research strategy and fecal metabolomics approach. Materials and methods: XYS was divided into two efficacy groups, i.e. the Shugan (SG) and the Jianpi (JP) groups, according to the efficacies of both XYS and the eight herbs recorded in the TCM theory and the research strategy of "Efficacy Compositions". A CUMS-induced depression model was constructed, where rats were randomly divided into 5 groups: negative control (NC), CUMS model (MS), XYS, SG, and JP. Multivariate data analysis including Principal Components Analysis (PCA) and Orthogonal Partial Least Squares-Discriminate Analysis (OPLS-DA) was utilized. Efficacy Index (EI) was calculated. Results: Metabolic profiling by PCA showed that XYS exhibited the strongest effect than the two efficacy groups, locating closest to the control group. OPLS-DA showed 10 metabolites were identified as potential biomarkers for the CUMS-induced depression. 8 potential biomarkers were significantly reversed by XYS while 5 and 4 biomarkers were reversed by SG and JP, respectively. The results of regulatory degrees showed that XYS had the highest EI than SG and JP. Concerning metabolic pathways, XYS regulated all the seven metabolic pathways associated with CUMS-induced depression, while SG and JP groups regulated six and three pathways, respectively. Conclusions: The antidepressant effect of XYS was stronger than that of SG and JP. The combined effects of SG and JP brought the integrated antidepressant effect of XYS. This study suggests that a combination of "Efficacy Compositions" strategy and metabolomics approach has great potentials in comprehensively and deeply understanding the scientific connotation of the compatibility rule of TCM prescriptions. Graphical abstract: Image 1 Highlights: "Efficacy Compositions" research strategy combined with metabolomics was employed. Xiaoyaosan was divided into two efficacy groups, i.e. Shugan and Jianpi groups. A fecal metabolomics approach coupled with multivariate data analysis was applied. The compatibility rule of XYS was demonstrated from metabolic profiles, metabolites and metabolic pathways. The efficacy index (EI) was calculated to quantitatively characteristic the anti-depression effects.